2004
DOI: 10.1093/occmed/kqh010
|View full text |Cite
|
Sign up to set email alerts
|

Bladder tumours in rubber workers: a factory study 1946-1995

Abstract: A statistically significant elevated risk of bladder cancer for the exposed workforce was evident, but this reversed when the carcinogen was removed from processing in October 1949. The use of morbidity (incidence) data in long-term studies of occupational bladder cancer should be the required methodology if the hazard and risk are not to be underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…To decrease the risk of occupational cancers, exposure control measures, such as the substitution of hazardous chemicals in the production process4 5 and measures to reduce exposure, have been introduced by the industry in the past decades 6 – 9. Vermeulen et al 7 showed a considerable reduction of almost 50 in inhalable dust concentrations over a 9-year period in the Dutch rubber industry (1988–1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To decrease the risk of occupational cancers, exposure control measures, such as the substitution of hazardous chemicals in the production process4 5 and measures to reduce exposure, have been introduced by the industry in the past decades 6 – 9. Vermeulen et al 7 showed a considerable reduction of almost 50 in inhalable dust concentrations over a 9-year period in the Dutch rubber industry (1988–1997).…”
mentioning
confidence: 99%
“…Due to the long latency time between carcinogen exposure and the manifestation of solid tumours for instance, the observed excess risk for urinary bladder cancer may still be related to exposure conditions encountered in the past, especially when β-naphthylamine was still used in the production process,5 and not to exposures experienced today 10. Conversely, any (remaining) cancer risks due to contemporary exposure would not be observed until a suitable latency period had elapsed.…”
mentioning
confidence: 99%
“…11 The absence of increased cancer risk in this cohort is consistent with multiple studies of recent entrants, that is, those exposed after control of β-naphthylamine exposure. 1,27,28 In particular, an Italian investigation found no significant excess risk of any cancer, except of pleura, in workers employed after 1940, reporting a similar number of observed and expected deaths from all cancers. 27 There was no excess cancer death in a cohort of recent entrant German rubber workers over the period 1981 to 2000.…”
Section: Discussionmentioning
confidence: 97%
“…15 Similarly, in a British study of rubber workers, bladder cancer risk was increased for workers exposed before 1950 (standardized registration rate = 171), whereas no association emerged in subjects exposed from 1950 onward (standardized registration rate = 102). 1 A Polish cohort study of rubber tire workers reported significantly lower cancer mortality (SMR = 67 in men) and total mortality (SMR = 72 in men) compared with the background population. 28 A meta-analysis of cohort studies of tire workers gave an overall relative risk of 0.88 (95% CI, 0.75 to 1.04) for all cancers and of 0.97 (95% CI, 0.58 to 1.63) for bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke contains carcinogenic benzo [a]pyrene, and the WHO energetically works to eliminate the smoking habit (2). As a result of industrial development, humans are now more exposed to mutagens and carcinogens; for example, workers in the rubber and coke production industries show higher cancer incidence (3,4). Nitrosamines in the rubber industry and benzo [a]pyrene for coke production have been identiˆed as probable carcinogens.…”
Section: Introductionmentioning
confidence: 99%